2013
DOI: 10.3923/pjbs.2014.62.67
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Concentration Relationship with Perna viridis Physical Properties in Mengkabong Lagoon, Sabah, Malaysia

Abstract: Perna viridis (P. viridis) has been identified as a good biological indicator in identifying environmental pollution, especially when there are various types of Heavy Metals Accumulations (HMA) inside its tissue. Based on the potential of P. viridis to accumulate heavy metals and the data on its physical properties, this study proffers to determine the relationships between both properties. The similarities of the physical properties are used to mathematical model their relationships, which included the size (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
2
0
1
Order By: Relevance
“…In green mussel, Pb level (1.04 µg/g) was comparable to the value of 1.12 µg/g and 0.96 µg/g reported by Ismail et al (2000) and Abdullah et al, (2014), respectively. Copper was higher (2.26 to 20.1 µg/g) than that reported by previous studies (Ismail et al, 2000;Kamaruzzaman et al, 2011;Abdullah et al, 2014) but lower than that observed by Denil et al (2017) in Marudu Bay (45.81 µg/g). The concentrations of Cr (20.27 µg/g), Mn (117.0 µg/g), Ni (14.74 µg/g) can be compared with the values documented earlier (Abdullah et al, 2014;Denil et al, 2017) which were 2.12 µg/g, 48.55 µg/g, 8.66 µg/g and 16.52-129.0 µg/g for Cr, Mn, Ni and Zn, respectively.…”
Section: Heavy Metal Bioaccumulation In Marsh Clam and Green Musselsupporting
confidence: 86%
See 2 more Smart Citations
“…In green mussel, Pb level (1.04 µg/g) was comparable to the value of 1.12 µg/g and 0.96 µg/g reported by Ismail et al (2000) and Abdullah et al, (2014), respectively. Copper was higher (2.26 to 20.1 µg/g) than that reported by previous studies (Ismail et al, 2000;Kamaruzzaman et al, 2011;Abdullah et al, 2014) but lower than that observed by Denil et al (2017) in Marudu Bay (45.81 µg/g). The concentrations of Cr (20.27 µg/g), Mn (117.0 µg/g), Ni (14.74 µg/g) can be compared with the values documented earlier (Abdullah et al, 2014;Denil et al, 2017) which were 2.12 µg/g, 48.55 µg/g, 8.66 µg/g and 16.52-129.0 µg/g for Cr, Mn, Ni and Zn, respectively.…”
Section: Heavy Metal Bioaccumulation In Marsh Clam and Green Musselsupporting
confidence: 86%
“…This study found Pb content (2.31 µg/g) lower than the previous studies (6.9-10.03 µg/g) conducted by Edward et al (2009) and Dabwan and Taufiq (2016). In green mussel, Pb level (1.04 µg/g) was comparable to the value of 1.12 µg/g and 0.96 µg/g reported by Ismail et al (2000) and Abdullah et al, (2014), respectively. Copper was higher (2.26 to 20.1 µg/g) than that reported by previous studies (Ismail et al, 2000;Kamaruzzaman et al, 2011;Abdullah et al, 2014) but lower than that observed by Denil et al (2017) in Marudu Bay (45.81 µg/g).…”
Section: Heavy Metal Bioaccumulation In Marsh Clam and Green Musselsupporting
confidence: 59%
See 1 more Smart Citation
“…Integrity in whatever undertakings should be emphasized and should become a compulsory to all. This study is also significant to increase the awareness of the integrity in the institution since public agencies are established with the primary objective of meeting the needs of people and the country (Abdullah and Abdullah, 2016). As Monson et al (2006) believed, a high-quality public service delivery system is required, where integrity should become a vital in creating efficient and disciplined public administration and services.…”
Section: Discussionmentioning
confidence: 95%
“…The importance of exhibiting integrity to fulfil one's responsibilities cannot be overestimated particularly from the perspective of a government sector. Public agencies are established with the primary objective of meeting the needs of people and the country (Abdullah and Abdullah, 2016). Monson et al (2006) believed that a high-quality public service delivery system is required, and integrity is vital in creating efficient and disciplined public administration and services to achieve the objective.…”
Section: Review Of Literaturementioning
confidence: 99%